A / B = 3 ---> A = 3B
A + 5B + 22 = 3B + 5B + 22 = 8B + 22 = 2 * ( 4B + 11 )
A + B + 11 = 3B + B + 11 = 4B + 11
( 2 * ( 4B + 11 ) ) / ( 4B + 11 ) = 2m
Пошаговое объяснение:
если можно лайк
2 m
A / B = 3 ---> A = 3B
A + 5B + 22 = 3B + 5B + 22 = 8B + 22 = 2 * ( 4B + 11 )
A + B + 11 = 3B + B + 11 = 4B + 11
( 2 * ( 4B + 11 ) ) / ( 4B + 11 ) = 2m
Пошаговое объяснение:
если можно лайк
2 m
Пошаговое объяснение:
A / B = 3 ---> A = 3B
A + 5B + 22 = 3B + 5B + 22 = 8B + 22 = 2 * ( 4B + 11 )
A + B + 11 = 3B + B + 11 = 4B + 11
( 2 * ( 4B + 11 ) ) / ( 4B + 11 ) = 2m